Perbandingan Pemikiran Imam Al Mawardi dan Imam Al Ghazali Tentang Adab Pendidik - Rusli Halomoan Pohan; Kadar Kadar; Alwizar Alwizar; Yusmaneli Yusmaneli; Husnel Nofrita; Sri Wahyuni Hakim (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2023)
This study aims to find out the Comparison of the Thoughts of Imam Al Mawardi and Imam Al Ghazali About Educator's Adab. This research needs to be done, bearing in mind that the main educator's etiquette is that it can be formed by the factor of an educator. This means that an educator becomes a major determinant for sustainability in that education. In this study the authors used library research methods or (library research). Namely research that originates from the results of library data collection because the objects of study are the Adabud dunya book written by Imam Al Mawardi and the book Ihya Ulumuddin, Bidayatul hidayah, Minhajul Abidin, Ayyuhal Walad, written by Imam Al Ghazali. Therefore, the data that is needed is textual data, namely books about the manners of educators contained in these books and books. The data collection technique in this study was by digging up information from literary sources, data sources that have been collected, both primary and secondary. The data analysis technique used in this study is content analysis (content analysis). The end result of this research is that the etiquette of educators according to Imam Al Mawardi is fear of Allah SWT, an educator must practice what he knows, the educator must say what he does not do, like to spread and teach his knowledge to people who are studying . Meanwhile, the etiquette of educators according to Imam Al Ghazali is fear of Allah SWT, educators must be humble, and may not be arrogant, accepting people who want to learn from him, both young and old, because a student of knowledge is a very noble person.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//